Implementasi Algoritma K-Means dalam Klasterisasi Penjualan Lauk Masakan Padang - Dewi Eka Putri; Dede Wira Trise Putra; Eka Praja Wiyata Mandala (STMIK Banjarbaru, 2025)
Culinary development in Indonesia is very rapid, increasing competition among culinary entrepreneurs. Side dish sales at RM Takana Juo are problematic in stock management due to lack of understanding of sales patterns. This research proposes the use of K-Means algorithm to cluster side dish sales based on parameters that focus on initial stock and number sold. This research begins with the collection of side dish sales datasets, determination of the optimal number of clusters, and application of the K-Means algorithm to group side dishes into two clusters: side dish clusters with higher initial stock and sales and side dish clusters with relatively low initial stock and sales. The results showed that the sales of 20 Padang cuisine side dishes at RM Takana Juo were successfully grouped into the two clusters. The validation of the method's performance showed an average Silhouette Score value of 0.57 which indicates that the K-Means algorithm successfully clustered the data quite well. This research contributes specifically in planning the procurement of Padang cuisine side dishes in organizing daily stock to reduce waste.Keywords: Clusterization; K-Means; Side Dish Sales; Padang Cuisine; Sales Pattern AbstrakPerkembangan kuliner di Indonesia sangat pesat sehingga meningkatkan persaingan antar pengusaha kuliner. Penjualan lauk di RM Takana Juo bermasalah dalam pengelolaan stok karena kurangnya pemahaman pola penjualan. Penelitian ini mengusulkan penggunaan algoritma K-Means untuk mengelompokkan penjualan lauk berdasarkan parameter yang fokus pada stok awal dan jumlah terjual. Penelitian ini dimulai dengan pengumpulan dataset penjualan lauk, penentuan jumlah klaster optimal, dan penerapan algoritma K-Means untuk mengelompokkan lauk ke dalam dua klaster yaitu klaster lauk dengan stok awal dan penjualan yang lebih tinggi dan klaster lauk dengan stok awal dan penjualan yang relatif rendah. Hasil penelitian menunjukkan bahwa penjualan 20 lauk masakan Padang di RM Takana Juo berhasil dikelompokkan ke dalam dua klaster tersebut. Validasi kinerja metode menunjukkan nilai rata-rata Silhouette Score sebesar 0.57 yang mengindikasikan bahwa algoritma K-Means berhasil mengelompokkan data dengan cukup baik. Penelitian ini berkontribusi spesifik dalam merencanakan pengadaan lauk masakan Padang dalam mengatur stok harian untuk mengurangi pemborosan.Kata kunci: Klasterisasi; K-Means; Penjualan Lauk; Masakan Padang; Pola Penjualan